THE INFLUENCE OF MOTIVATION AND ORGANIZATIONAL COMMITMENT ON DISCIPLINE IN TRABAS ORGANIZATION - Naftali Shieva; Fetty Poerwita Sary (Journal of Economic, Bussines and Accounting (COSTING), 2024)
As the only one motor-trail adventure organization in Bandung, TRABAS has an exclusive impression among the bike-lovers. Therefore, the recruitment for new members increases from period to period. Up to today, TRABAS has 1204 members since it was established in 1995. However, the large number of new members does not align with the high participation in signature activities of TRABAS. This research aims to find out how motivation and organizational commitment affect discipline in TRABAS Organization. The research method used is a descriptive method with data collection techniques, namely a questionnaire with a population of 270 organizational administrators in Bandung Raya, and utilizing a purposive sampling method with the Slovin formula to determine the sample size, namely 72 organizational administrators. This research also uses PLS-SEM with the help of Smart-PLS 4. The result of the study based on the descriptive analysis shows that motivation, organizational commitment, and discipline is included in good category. Meanwhile, based on the PLS-SEM Analysis, H1: P-value of 0,000 < 0,05 and the T-statistic value is 3,312 > 1,96, means that H1 is accepted and H2: P-value of 0,001 < 0,05 and the T-statistic value is 5,586 > 1,96, means that H2 is also accepted. The conclusion is motivation, organizational commitment, and discipline in TRABAS is good. In addition, there is an impact from motivation and commitment on discipline in TRABAS organization.